PEGylated MoS2 Nanosheets: A Dual Functional Photocatalyst for Photodegradation of Organic Dyes and Photoreduction of Chromium from Aqueous Solution - Madima Ntakadzeni; William Wilson Anku; Neeraj Kumar; Penny Poomani Govender; Leelakrishna Reddy (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2019)
This article reports the synthesis of PEGylated microspheres of MoS2 nanosheets through the hydrothermal method and its application in rhodamine B and methylene blue dyes photodegradation, and photoreduction of chromium(VI) to chromium(III) in water under illumination with visible light. The catalyst was characterized using X-ray Diffraction (XRD), Transmission Electron Microscopy (TEM), Field Emission Scanning Electron Microscopy (FESEM), Energy Dispersive X-ray Spectroscopy (EDS), Fourier Transform Infra Red (FTIR), Thermo-gravimetric Analysis (TGA), and UV-Vis spectroscopies. XRD result reveals the MoS2 nanosheets to be present in the hexagonal phase of MoS2. SEM, TEM, and HRTEM images show that the synthesised sample has spherical shapes made up of several thin sheets of MoS2. The catalyst showed visible light responsivity with a calculated band gap of 1.92 eV. The MoS2 nanosheets exhibited high degradation efficiency against both dyes. The RhB and MB dyes experienced degradation efficiencies of 97.30 % (RhB) and 98.05 % (MB) in 75 min 90 min, respectively. The MoS2 photocatalyst is also observed to be effective in photocatalytic reduction of Cr(VI) and displayed 91.05% reduction of Cr(VI) to Cr(III) in 75 min. The results reveal that the synthesised MoS2 nanosheet is a good photocatalytic material for degradation of dyes and reduction of Cr(VI) to Cr(III) in water.